The Hate U Give - Thomas, Angie (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
"Sixteen-year-old Starr Carter moves between two worlds: the poor neighborhood where she lives and the fancy suburban prep school she attends. The uneasy balance between these worlds is shattered when Starr witnesses the fatal shooting of her childhood best friend Khalil at the hands of a police officer. Khalil was unarmed. Soon afterward, his death is a national headline. Some are calling him a thug, maybe even a drug dealer and a gangbanger. Protesters are taking to the streets in Khalils name. Some cops and the local drug lord try to intimidate Starr and her family. What everyone wants to know is: what really went down that night? And the only person alive who can answer that is Starr. But what Starr does or does not say could upend her community. It could also endanger her life"--
Accelerated Reader
Reading Counts!
AR
Accelerated Reader AR
Keywords: Racism -- United States; Fiction; Witnesses -- United States; Fiction; African American teenagers -- Fiction; Race relations -- Fiction; Police shootings -- United States; Fiction; Police-community relations -- United States; Fiction; Racism -- Fiction; Race relations -- Fiction; African American teenagers -- Fiction; Police shootings -- Fiction; Witnesses -- Fiction; novels; Novels; Fiction; Juvenile works; Urban fiction; Young adult works; Novels; Urban fiction; Fiction; Romans